Gender-Responsive Strategies in Highland Farming: Evaluating Women Empowerment in Indonesia - Chairani Putri Pratiwi; Ramadhona Saville; Katsumori Hatanaka; Nina N. Shimoguchi (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Women farmers in regions such as Cianjur and Tabanan, Indonesia, consistently face systemic challenges, including limited access to resources and decision-making power, which can hinder their productivity and well-being.Purpose: This study evaluates innovative strategies to enhance women's empowerment in highland agriculture by focusing on empowering women to play a more significant role.Design/methodology/approach: This study employed a combined methodological approach, utilizing the women’s Empowerment in Agriculture Index (WEAI) framework and integrating the Analytic Hierarchy Process (AHP) to evaluate the empowerment factors. This study utilized five domains for AHP-WEAI: production decisions, resource access, income control, leadership participation, and time allocation. Findings/Results: This study identified key factors that significantly influence women’s empowerment, such as access to credit and leadership roles. Economic factors (credit/land access) dominated in Cianjur (AHP weight: 0.45), while social factors (leadership roles) were significant in Tabanan (0.40). Conclusion: This study identifies key factors influencing women's empowerment in Cianjur and Tabanan, using the AHP-WEAI framework. These findings highlight the need for region-specific strategies, such as economic interventions in Cianjur and social capital building in Tabanan, to enhance women's roles in highland farming systems.Originality/value (State of the art): This study offers a novel approach to quantify domain-specific empowerment drivers in Indonesian highlands using AHP-WEAI integration. Keywords: women's empowerment, agribusiness management, food security, climate change, sustainable agriculture